# [SOLVED]Arranging Formula

#### dipster307

##### New member
I am having problems trying arrange the formula below. I want to change it so the formula starts with "M35" equals to.

18733.59 = M35-(((M35-I41)*I40)+((M35-M36)*I39))

The equation above is use in MS Excel, this is why you see the variable M35, I41 etc.

Now the values used to get the value 18733.59 is as follows:

M35 = 23823.52
M36 = 8105
I40 = 0.12
I41 = 7605
I39 = 0.2

Say if 18733.59 is equal to X. I used the formula to calculate X as I know all the values. But I want to arrange the formula to calculate M35, so I I know the value of X and I don't know the value of M35, I can calculate it, if I had the formula re-arrange, I could than calculate it.

#### CaptainBlack

##### Well-known member
I am having problems trying arrange the formula below. I want to change it so the formula starts with "M35" equals to.

18733.59 = M35-(((M35-I41)*I40)+((M35-M36)*I39))

The equation above is use in MS Excel, this is why you see the variable M35, I41 etc.

Now the values used to get the value 18733.59 is as follows:

M35 = 23823.52
M36 = 8105
I40 = 0.12
I41 = 7605
I39 = 0.2

Say if 18733.59 is equal to X. I used the formula to calculate X as I know all the values. But I want to arrange the formula to calculate M35, so I I know the value of X and I don't know the value of M35, I can calculate it, if I had the formula re-arrange, I could than calculate it.

X = M35-(((M35-I41)*I40)+((M35-M36)*I39))

First you have a redundant set of brackets, so we get rid of them:

X = M35 - ((M35-I41)*I40) - ((M35-M36)*I39)

Expand the brackets:

X = M35 - M35*I40 + I41*I40 - M35*I39 + M36*I39

Now collect the terms with M35:

X = M35*(1 - I40 - I39) + I41*I40 + M36*I39

so:

M35*(1 - I40 - I39) = X - I41*I40 - M36*I39

giving:

M35 = (X - I41*I40 - M36*I39) / (1 - I40 - I39)

CB

Last edited:
• Sudharaka

#### dipster307

##### New member
Sounds like a good answer, however this is my problem.

M35 = 23823.52 and X = 18733.59

These values are correct and can't be changed.

So when I use your formula, your answer. I put in X and do the calculation, I get 16689.99 and not 18733.59.

Using the BODMAS.

I am doing something wrong or is there an error in your solution?

#### Wilmer

##### In Memoriam
a=M35, b=M36, c=I39, d=I40, e=I41

a = (x - bc - de) / (1 - c - d)
a = 23823.514705882.....

CB has a couple of sign typoes...

• CaptainBlack and Sudharaka

#### Wilmer

##### In Memoriam
Not any more, thanks
CB
You still need to stand in the corner for 15 minutes !

• dipster307